Experimental-Morphological Study of Reparative Bone Formation with The Replacement of The Cavity Defect of The Bone with A Mesh of Titanium Nickelide - Iryanov, Yu.M.; Kiryanov, N.A. (International Journal of Human Anatomy, 2018)
Purpose of Study To study reparative osteogenesis and tissue integration characteristics for implanting three-dimensional mesh structures of titanium nickelide into a bone cavitary defect. Material and Methods The authors modeled cavitary defects of femoral metaphysis experimentally in Wistar rats divided into an experimental group and control one. The study duration was 60 days in total. The methods of radiography, those of light and electron microscopy, X-ray electron probe microanalysis used. Results Under implantation the defect was filled with cancellous bone the volumetric density of which more than 1,5-fold exceeded control values (р < 0.001). The implant had biocompatibility, osteoconductive and osteoinductive properties, it stopped inflammatory processes. The membrane protective barrier which prevented connective tissue sprouting was formed on the implant surface in the defect periosteal zone. The osteointegrative junction was formed being persisted up to the end of the experiment. Reparative osteogenesis was performed by direct intramembranous and apposition type. Conclusion The implant of three-dimensional mesh titaium-nickelide structures has marked osteoplastic properties, and it can be successfully used in orthopedic surgery.
Keywords: reparative osteogenesis; bone defect; implant; titanium nickelide.